Environmentally specific servant leadership and voluntary pro-environmental behavior in the context of green operations: A serial mediation path - Zafar, Hina; Tian, Feng; Ho, Jo Ann; Zhang, Gaoqi (Frontiers in Psychology, 2022)
Green operations of organizations and enhancement of corporate social responsibility hinges upon leaders. This study investigated the influential role performed by environmentally specific servant leadership in provoking voluntary pro-environmental behavior of employees. The findings illuminate a serial chain mediation model that originates as a result of environmentally specific servant leadership and leads toward psychological empowerment, and organizational identity, ultimately leading towards voluntary pro-environmental behavior. Data from the textile sector of Pakistan uncovered that environmentally specific servant leadership prompted the voluntary pro-environmental behavior of employees. Moreover, environmentally specific servant leadership was significantly linked with voluntary pro-environmental behavior through psychological empowerment. The study supports the serial mediation of psychological empowerment and organizational identity in stirring voluntary pro-environmental behavior. An organizational psychological mechanism has been unraveled that can help organizations achieve a high level of sustainability and can serve as a catalyst for organizational green operations.